Translation of the UK Pediatric Influenza Vaccination Programme in Primary Schools to 13 European Countries Using a Dynamic Transmission Model - Laetitia Gerlier; Judith Hackett; Richard Lawson; Sofia Dos Santos Mendes; Martin Eichner (Journal of Health Economics and Outcomes Research)
# Objectives To simulate the impact of a pediatric influenza vaccination programme using quadrivalent live attenuated influenza vaccine (QLAIV) in Europe by applying coverage rates achieved in the United Kingdom during the 2014–2015 season and to compare the model outcomes to the UK results.